Translation Quality in Translating Abstract in Thesis from the Economics Field - Fadilla, Dwi; Ardi, Havid; Mahmud, Rashed (English Department, Faculty of Humanities, Andalas University, 2024)
A scientific research report should provide abstract at the beginning of themanuscript. Students who learn English as a foreign language in Indonesiais also provided with the translation skill, including in translating abstract.This study aims to analyze the translation quality of the thesis abstracttranslated by the English literature students of UNP. This research usedthe descriptive method as the research design. The population of thisstudy consisted of sixth-semester English literature students of UNP,and the purposive sampling method was used to select 25 students as thesample. A translation test was used to collect data. Based on the resultsof the analysis of the translation quality, the researcher concludes thatthe students’ accuracy, acceptability, and readability of the abstract in thethesis for students of English Literature who have studied translation is lessaccurate, less acceptable, and has a high readability translation level. Thelevel of accuracy is at an average of 2.14. The level of acceptability is at anaverage of 2.34. Moreover, the level of readability is at an average of 2.71.